Socialization of the Importance of Financial Record Keeping for MSMEs - Lating, Ade Irma Suryani; Buchori, Imam; Muflihin, Mohammad Dliyaul; Rahayu, Hastanti Agustin; Aripratiwi, Ratna Anggraini; Romaisyah, Luqita; Susanto, Febry Fabian (Sahwahita: Community Engagement Journal, 2025)
This community service program aims to enhance the financial literacy of Micro, Small, and Medium Enterprises (MSMEs) in Kampung Jajan, Brebek Village, Sidoarjo, by strengthening their capacity for basic financial record keeping. Utilizing a participatory approach, the program implemented a series of targeted training sessions and personalized mentoring activities over a two-month period, involving 25 MSME participants. Pre- and post-program assessments revealed a measurable increase in participants’ understanding of the importance of financial records, as indicated by a 40% average improvement in basic accounting comprehension scores. However, the intervention also identified persistent challenges, including low awareness of financial documentation benefits, the relatively older demographic of MSME actors, and limited formal education levels. While the program demonstrated short-term improvements in financial knowledge and attitudes, further interventions are necessary to ensure behavioral change, including continuous mentoring, the development of context-based accounting modules, and collaboration with local government units to institutionalize financial training support.